2017
DOI: 10.1158/1078-0432.ccr-16-3275
|View full text |Cite
|
Sign up to set email alerts
|

Re-engineering the Pancreas Tumor Microenvironment: A "Regenerative Program" Hacked

Abstract: The “hallmarks” of pancreatic ductal adenocarcinoma (PDAC) include proliferative, invasive and metastatic tumor cells and an associated dense desmoplasia comprised of fibroblasts, pancreatic stellate cells, extracellular matrix and immune cells. The oncogenically-activated pancreatic epithelium and its associated stroma are obligatorily interdependent, with the resulting inflammatory and immune-suppressive microenvironment contributing greatly to the evolution and maintenance of PDAC. The peculiar pancreas-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 70 publications
1
29
0
Order By: Relevance
“…We and others have demonstrated that low dose cyclophosphamide can also deplete Tregs, modulate the TME and maximize clinical responses to immunotherapy (123,127,128). Another approach is combination therapy with epigenetic modulators, as epigenetic therapy appears to be immunomodulatory (129), and epigenetic therapy in PDAC is reviewed by Evan and colleagues in this CCR focus issue (130). Immunotherapies in clinical development for PDAC in combination with standard chemotherapy include the indoleamine 2,3 dioxygenase (IDO) inhibitor indoximod, the bruton tyrosine kinase (BTK) inhibitor ibrutinib, CD-40 agonists, and CCR2 inhibitors (Table 1).…”
Section: Vaccine Immunotherapy Strategies For Pdac Treatmentmentioning
confidence: 99%
“…We and others have demonstrated that low dose cyclophosphamide can also deplete Tregs, modulate the TME and maximize clinical responses to immunotherapy (123,127,128). Another approach is combination therapy with epigenetic modulators, as epigenetic therapy appears to be immunomodulatory (129), and epigenetic therapy in PDAC is reviewed by Evan and colleagues in this CCR focus issue (130). Immunotherapies in clinical development for PDAC in combination with standard chemotherapy include the indoleamine 2,3 dioxygenase (IDO) inhibitor indoximod, the bruton tyrosine kinase (BTK) inhibitor ibrutinib, CD-40 agonists, and CCR2 inhibitors (Table 1).…”
Section: Vaccine Immunotherapy Strategies For Pdac Treatmentmentioning
confidence: 99%
“…73 The abnormal expression of MYC in many cancers, including PDAC, is usually not due to dysfunction of the MYC gene itself, but is caused, for example, by amplification, chromosomal translocation, or upstream carcinogenic signaling disorders, as well as by a loss of tumor suppressor factors. 74,75 MYC is required for the maturation and maintenance of embryonic and adult acinar differentiation, and the activation of MYC signaling induces cancerous changes in pancreatic tissue. 76 MYC overexpression occurs in up to 42% of late PDAC, which is associated with poor clinical outcomes, increased probability of recurrence, worsening disease, and decreased survival in patients with PDAC.…”
Section: Mycmentioning
confidence: 99%
“…Normal pancreatic tissue has the potential to regenerate after injury in a process involving the activation of stellate cells and fibrosis that isolates the affected area, protects healthy tissue, and resolves after tissue repair. Cancer cells disrupt this regenerative procedure by causing the continuous activation of stellate cells with subsequent excessive stroma production, contributing to tumor growth and disease progression [30]. Invasive pancreatic cancer evolves in a step-wise pattern from precursor lesions, most commonly initiated by pancreatic intraepithelial neoplasia.…”
Section: The Pancreatic Ductal Adenocarcinoma Microenvironmentmentioning
confidence: 99%